PERANCANGAN DAN IMPLEMENTASI APLIKASI KEAMANAN UJIAN ONLINE MENGGUNAKAN ALGORITMA RIJNDAEL DAN REMOTE DESKTOP PROTOCOL - Alamsyah, Zaenal; Insany, Gina Purnama; Taqwana, Friendly Jihad (SKANIKA: Sistem Komputer dan Teknik Informatika, 2024)
Hanna Hersop Course and Training Institute (LKP) is a non-formal educational institution that offers learning materials both offline and online. The obstacles faced by the institution during the implementation of the exam are still not optimal because they are still carried out using conventional methods, such as the use of paper and pencils, which causes the risk of cheating and security during the exam. So this study aims to implement an exam system on a virtual machine with an integrated security application using the Remote Desktop Protocol (RDP) with the Windows Server 2019 operating system as a server and client for the implementation of the exam test. The main objectives include security settings on the Windows Server OS in the virtual machine, login key encryption with the Rijndael algorithm, and creating an application to generate login keys. The development technique chosen is Rapid Application Development (RAD). The online exam application was developed using Microsoft ASP.NET Core for the time server, while the exam website uses PHP and JavaScript. The desktop application of the security system with RDP was created using the C# programming language. This system includes setting the exam time synchronized with the time server via the HTTP protocol, as well as restricting access to the exam website only in the virtual machine and limiting keyboard functionality during the exam. The results of the study show that the implementation of online exams on a virtual machine with an RDP security system can create a safe exam environment. This includes preventing cheating through restricting access to applications and the web, encrypting login keys to maintain confidentiality of information, and limiting keyboard functionality. This implementation also creates a better exam implementation structure with exam time synchronization, and a high level of user satisfaction. Respondents on the Likert scale showed satisfaction with the ease of use of the online exam security application implemented at LKP Hanna Hersop.